Efficacy of Acute Cellular Rejection Treatment According to Banff Score in Kidney Transplant Recipients: A Systematic Review. Issue 12 (December 2016) - Lamarche, Caroline; Côté, Jean-Maxime; Sénécal, Lynne; Cardinal, Héloïse
Abstract : Background: The poor prognosis classically associated with Banff grade 2 acute cell-mediated rejection (CMR) may be due to unrecognized antibody-mediated damage. We thus performed a systematic review of the literature to determine the rate of response to treatment in kidney transplant recipients with pure CMR, stratified by Banff class. Methods: In addition to a manual search, databases interrogated included Excerpta Medica Database (EMBASE), Medical Literature Analysis and Retrieval System Online (MEDLINE), Evidence-Based Medicine (EBM) databases, Central, PubMed and CINAHL. Studies providing functional and/or histological response rates to the treatment of CMR rejection by Banff class (1997 or more recent) were included. Results: Among the 746 articles identified, 5 articles were included in the final review. Two studies excluded some, and 2 excluded all features of antibody-mediated rejection, while providing data on functional recovery. The absence of functional recovery was reported in 4% of borderline, 15% for Banff grade 1A and IB pooled, 0% to 25% of Banff grade 1B alone, 11% to 20% of Banff grade 2A, and 38% of Banff grade 2B rejections. Conclusions: The rate of functional recovery of pure Banff IIA CMR overlapped with that of Banff grade 1 CMR, whereas Banff grade 2B showed worse prognosis. There was important heterogeneity in the definition of response to treatment and paucity of data describing the histological response to treatment stratified by Banff class. There is a pressing need to standardize outcome metrics for the reversibility of rejection in kidney transplant recipients in order to design high-quality trials for novel therapeutic alternatives. Abstract : Supplemental digital content is available in the text.